A QUALITATIVE STUDY OF CUSTOMER PERCEPTION WITHIN MODOINDING MARKET DURING THE COVID-19 PANDEMIC - Geofano Felascho Komaling; Joyce Lapian; Regina Saerang (Universitas Sam Ratulangi, 2022)
Pasar Modoinding is one of the well-known traditional market in North Sulawesi, especially in South Minahasa region. The current condition of Pasar Modoinding now also is directed in a positive way with the idea of modernizing the market in order to attract more customers. The main problem now is regarding the customer perception of Pasar Modoinding during the Covid-19 Pandemic, despite the development of market that will be done in the near future. The problem risen regarding customer perception because of the status quo of traditional market itself, during the pandemic most of people are afraid to go out from home because of the virus that can easily spread. The purpose of this study is to see about the customer perception during Covid-19 Pandemic, in this case within the Modoinding Market. The result shows that customer perception which can be measured with 3 main aspects such as perceived risk, perceived value and perceived quality can shift the perception especially during the pandemic. Based on the result, the researcher provided recommendation which is to adapt with the current condition of Covid-19 pandemic by looking upon the health protocol and also other aspects during the pandemic.Â